Ragam Arsitektur Masjid Tradisional Banjar Kalimantan Selatan dan Makna Simbolisnya - Wajidi (Jurnal Kebijakan Pembangunan, 2017)
The traditional Banjar mosque in South Kalimantan is interesting to study because in addition to having diversity in architectural model that is relatively the same, it also contains a symbolic meaning as a reflection of the influence of pre-Islamic culture in the construction and the decoration. This study aims to: (1) find out the Banjar traditional mosque construction; (2) find out the effect of pre-Islamic ornamentation that reflects the relationship between Islam and the culture of Banjar traditional mosque architecture. The location of research is in Banjarmasin, Tapin regency, Hulu Sungai Selatan regency, and Tabalong regency in which the mosques are categorized as the traditional Banjar mosque. This study is a qualitative descriptive study with an anthropological, historical, cultural and, religious approach method. The results showed that even though all mosques in Banjar have the same roof overlapping, the traditional Banjar mosques have differences from the other Indonesian traditional mosques. The difference is mainly in the form of variations roof, floor construction stage, carving or decoration (ornaments) that each is influenced by the local culture and environment. Abstrak Masjid tradisional Banjar Kalimantan Selatan menarik untuk dikaji karena selain memiliki keragaman modelarsitektur yang relatif sama, juga mengandung makna simbolis sebagai cerminan adanya pengaruh budayapra-Islam dalam konstruksi dan ragam hiasnya. Kajian ini bertujuan untuk: (1) Mengetahui gambarankonstruksi masjid tradisonal Banjar; (2) Mengetahui pengaruh ragam hias pra-Islam yang mencerminkanhubungan antara Islam dan budaya pada arsitektur masjid tradisional Banjar. Penelitian ini mengambiltempat di Kota Banjarmasin, Kabupaten Tapin, Kabupaten Hulu Sungai Selatan, dan Kabupaten Tabalongyaitu di tempat masjid tradisional Banjar berada. Penelitian ini merupakan penelitian deskriptif kualitatifdengan metode pendekatan antropologis, sejarah, budaya dan keagamaan. Hasil penelitian menunjukkanbahwa meski sama-sama beratap tumpang (bertingkat), masjid tradisional Banjar di Kalimantan Selatanmempunyai perbedaan dengan masjid tradisional Indonesia lainnya. Perbedaan tersebut terutama dalamvariasi bentuk atap, kontruksi lantai panggung, ukiran atau ragam hias (ornamen) yang masing-masingdipengaruhi oleh budaya dan lingkungan setempat.